Students' Ability in Using Context Clues at English Education Program UNP - Muliya, Zahrani Esa; Zainil, Yetti (Universitas Negeri Padang, 2024)
This research aims to find out the abilities of the first-year and the third-year students of English Education Program of Universitas Negeri Padang in using Context Clues and to know the difficulties faced by the students in using Context Clues. This research was a descriptive research. The population of this research were the first-year and third-year students of English Education Program UNP. The total sample of this research was 80 students consisting of 45 first-year students and 35 third-year students. The instrumentations of this research were Context Clues test consisting of 30 questions and an interview. The test result showed that the average score of first-year students was 51.3 and the third-year students was 54.7. The average score indicated that the students’ ability in using Context Clues was in Moderate level. Furthermore, the interview result showed that there were three difficulties faced by the students in using Context Clues: not understanding the context of the sentence, lacking vocabulary mastery, and having difficulty in finding the meaning of unfamiliar words by using Example and Antonym clues.